Lobophora (Dictyotales) Species Richness, Ecology and Biogeography Across the North‐Eastern Atlantic Archipelagos and Description of Two New Species1. Issue 2 (10th February 2020) - Vieira, Christophe; Henriques, Filipe; D'hondt, Sofie; Neto, Ana; Almada, Carmen H.; Kaufmann, Manfred; Sansón, Marta; Sangil, Carlos; Clerck, Olivier De
Abstract : The brown alga Lobophora (Dictyotales, Phaeophyceae) is an important macroalga in the North ‐ eastern Atlantic archipelagos (i.e., Macaronesia). Notably in the Canaries it can dominate benthic assemblages. While the genus has been the subject of several ecological studies in the Canaries, no study has yet been conducted to assess species‐level diversity of Lobophora in Macaronesia. We reassessed the diversity of Lobophora in Macaronesia, reporting the presence of seven species ( L. caboverdeana sp. nov., L. canariensis, L . dagamae sp. nov., L . delicata, L. dispersa, L. littlerorum, and L. schneideri ) . Lobophora spp. from Macaronesia are morphologically and ecologically distinguishable. In the Canaries, L. schneideri dominates the photophilic assemblages from the intertidal to 20‐30 m depth. Lobophora dagamae sp. nov. grows in less illuminated shallow habitats, and replaces L. schneideri from 30 to 80 m. Lobophora canariensis also has a wide vertical distribution, from the intertidal to deep waters, while L. delicata, L. dispersa and L. littlerorum grow in shallow waters. The dominance of species with an upright habit versus prostrate or crustose species may be mediated by the pressure of herbivores. Four species have an amphi‐Atlantic distribution: L. littlerorum, L. canariensis, L. delicata, and L. schneideri . Lobophora schneideri and L. delicata are furthermore distributed in the Mediterranean Sea. By sampling a pivotal region in the Atlantic, this study significantly improves our knowledge of Lobophora biogeography in the Atlantic Ocean. Macaronesia constitutes a species–poor region for Lobophora where no diversification events occurred, and a region of overlap between the Greater Caribbean and the Indo‐Pacific.